Library Automated Self-service Machine (LASM) - ICC - Jantan, Azizi (Perpustakaan Tun Abdul Razak, 2009)
This Self-service station flexible package that allows library customers to manage their own transactions easily and efficiently. Deliver self-service that’s user friendly, faster and amazingly simple to use and maintain.